Effect of initial inoculum on growth and fatty acid content as an Î±-glucosidase inhibitor in Colletotrichum sp. TSC13 mycelium that cultures under shake and static conditions - Nina Artanti; Leonardus B.S. Kardono; Sanro Tachibana (Jurnal Kimia Terapan Indonesia, 2017)
Colletotrichum species were reported producing various bioactive compounds that may potentially be used in the development of anti-microbial, antioxidant, anticancer and anti-diabetes drugs. Our previous studies showed that the methanol extracts of mycelia from Colletotrichum sp. TSC13, an endophytic fungus isolated from Taxus sumatrana (Miq.) de Laub., were found to have Î±-glucosidase inhibitory activities. The aim of present study was to examine the effects of initial inoculum on growth and the content of fatty acids as an Î±-glucosidase inhibitor in Colletotrichum sp. TSC13 that grew under shake and static condition. The results showed that shake and static conditions had more effect compared to the initial inocculum on growth and glucose consumption in growth and glucose consumption. However in terms of fatty acids contents and Î±-glucosidase inhibitor activities the initial inoculum showed more effect than shake and static conditions